Attitude and The Moral Value development of Teenage Students - Besari, Amam (STAI MA'ARIF MAGETAN, INDONESIA, 2021)
The behavior of adolescents at this time has become the center of attention to be studied. Especially in matters of morality and behavior. The background that underlies this is that there are differences in morals and attitudes that adolescents have today with adolescents in the past. Youth in the past prioritized morals, so that their politeness patterns were more awake. Adolescents today, with the development of globalization, prioritize ego, which has an impact on the emergence of an attitude of wanting to win alone, not wanting to admit mistakes. Globalization is a characteristic of the relationships between the inhabitants of the earth that go beyond conventional boundaries, such as nations and states. With this there is no longer a barrier that can be used as a boundary by a country so that there will be acculturation (mixing of cultures) between Western culture and Indonesian culture which has differences fundamental. There was a cultural clash between western cultures which tended to prioritize liberalism and uphold freedom, freedom in any case. Different with Indonesia, as a country that holds religious understanding. As a result, many Indonesian adolescents who do not have a strong grip are unable to filter out western culture which in turn erodes the noble values of the nation's culture.